Trends and innovations in agricultural mechanization: increasing sustainability and energy efficiency in livestock farming (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
Modern trends and challenges of livestock mechanization are considered with an emphasis on the introduction of innovative technologies, energy efficiency and sustainable development. The use of automated systems, precision agriculture, renewable energy sources, such as biogas plants, solar panels and geothermal systems, is analyzed. Particular attention is paid to environmental, economic and social aspects of sustainable development. The prospects for the integration of digital technologies, artificial intelligence and the expansion of new markets are identified, in particular in the production of organic fertilizers and bioenergy. The results of the study demonstrate that the implementation of an integrated approach to mechanization contributes to increasing productivity, reducing costs and minimizing the negative impact on the environment, ensuring the long-term sustainability of the industry. Keywords: livestock mechanization, innovative technologies, energy efficiency, sustainability, renewable energy sources, automation, waste processing, precision agriculture, environmental sustainability, economic sustainability, digital technologies.
Keywords: livestock mechanization; innovative technologies; energy efficiency; sustainability; renewable energy sources; automation; waste processing; precision agriculture; environmental sustainability; digital technologies